Real-time nonlinear MPC and MHE for a large-scale mechatronic application. (December 2015) - Vukov, M.; Gros, S.; Horn, G.; Frison, G.; Geebelen, K.; Jørgensen, J.B.; Swevers, J.; Diehl, M.
Abstract: Progress in optimization algorithms and in computational hardware made deployment of Nonlinear Model Predictive Control (NMPC) and Moving Horizon Estimation (MHE) possible to mechatronic applications. This paper aims to assess the computational performance of NMPC and MHE for rotational start-up of Airborne Wind Energy systems. The capabilities offered by an automatic code generation tool are experimentally verified on a real physical system, using a model comprising 27 states and 4 inputs at a sampling frequency of 25 Hz. The results show the feedback times less than 5 ms for the NMPC with more than 1500 variables. Abstract : Highlights: We study a combined nonlinear MPC and MHE scheme for an Airborne Wind Energy system. Fast MPC and MHE solvers are auto-generated using the ACADO Code Generation Tool. Two variants of MPC solvers are experimentally verified on a real physical system. The QP underlying the MPC with more than 1500 variables can be solved in under 5 ms.